2021
DOI: 10.1186/s12885-021-08318-1
|View full text |Cite
|
Sign up to set email alerts
|

Highly heterogeneous-related genes of triple-negative breast cancer: potential diagnostic and prognostic biomarkers

Abstract: Background Triple-negative breast cancer (TNBC) is a highly heterogeneous subtype of breast cancer, showing aggressive clinical behaviors and poor outcomes. It urgently needs new therapeutic strategies to improve the prognosis of TNBC. Bioinformatics analyses have been widely used to identify potential biomarkers for facilitating TNBC diagnosis and management. Methods We identified potential biomarkers and analyzed their diagnostic and prognostic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 79 publications
(69 reference statements)
1
9
0
Order By: Relevance
“…Consistently, a decrease in FAM83B expression was also found in the metastatic tissue with respect to the corresponding primary tumor, which was more evident and significant in distant metastases from FTCs, than in locoregional recurrences from PTCs. Moreover, patients with low FAM83B levels tended to have a higher frequency of distant metastatization and a shorter DFS rate than those with high levels, further highlighting the correlation between dedifferentiation and low FAM83B mRNA levels, and consistent with data found in ovarian cancer 8 , in lung squamous cell carcinoma—SCC 9 , and triple-negative breast cancer 20 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistently, a decrease in FAM83B expression was also found in the metastatic tissue with respect to the corresponding primary tumor, which was more evident and significant in distant metastases from FTCs, than in locoregional recurrences from PTCs. Moreover, patients with low FAM83B levels tended to have a higher frequency of distant metastatization and a shorter DFS rate than those with high levels, further highlighting the correlation between dedifferentiation and low FAM83B mRNA levels, and consistent with data found in ovarian cancer 8 , in lung squamous cell carcinoma—SCC 9 , and triple-negative breast cancer 20 .…”
Section: Discussionsupporting
confidence: 83%
“…FAM83A , FAM83D , FAM83G , and FAM83H ) have been reported to be involved in the regulation of cell migration in different tumors (osteosarcoma, endometrial, colon, cervical and gastric cancer) 12 , 15 19 . On the other hand, it has been very recently reported that ovarian cancer patients with low FAM83B levels have shorter survival time and show cisplatin resistance 8 , while high expression of FAM83B correlates with prolonged progression-free interval in triple negative breast cancer 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several prognostic factors have been identified in previous research with the aim of helping decision-making in pursuit of tailored individual care for TNBC patients. Yiduo Liu et al screened four heterogeneous-related genes (FAM83B, KITLG, RBM24, and S100B) from 105 genes to construct a prognostic signature in the disease-free interval (DFI) of TNBC (16). Chao Li et al identified a prognosis-related signature associated with energy metabolism including eight energy metabolism-associated genes (IL1RL2, FBLN7, CA3, PDE1B, SLURP1, CILP, AQP7, and TPSB) in triple-negative breast cancer (17).…”
Section: Discussionmentioning
confidence: 99%
“…For example, survival analyses suggest that RBM24 may be a potential prognostic biomarker for head and neck squamous cell carcinoma (HNSCC) and skin cutaneous melanoma (SKCM) patients [ 58 , 59 ]. In triple negative breast cancer (TNBC) patients, RBM24 is upregulated during the disease-free interval (DFI) and is correlated with poor prognosis [ 34 ]. In medulloblastoma (MB), RBM24 represents one of the few reliable biomarkers that can be used for diagnosis and prognosis of group 4 tumors [ 60 ].…”
Section: Rbm24 In Cancer Developmentmentioning
confidence: 99%
“…Functional and correlative analyses suggest that it displays either anti-oncogenic or oncogenic potential. Several studies suggest that it suppresses tumor progression [ 28 , 29 , 30 , 31 , 32 ], while others indicate that its upregulation promotes tumor growth [ 33 , 34 , 35 , 36 , 37 ]. These raise the possibility that RBM24 may act either as a tumor suppressor or as an oncogene, functioning in a context- or background-dependent manner.…”
Section: Introductionmentioning
confidence: 99%